2004
DOI: 10.1002/jcu.20008
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of computerized gray‐scale sonographic findings with thyroid function and thyroid autoimmune activity in patients with Hashimoto's thyroiditis

Abstract: Computerized gray-scale sonography provides an objective measure of thyroid hypoechogenicity, which correlates well to the clinical stages of HT. Use of this modality may prove beneficial in the diagnosis and follow-up of patients with HT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 25 publications
1
39
0
4
Order By: Relevance
“…The interface between thyroid cells and the colloid exhibits an elevated acoustic impedance, causing high-frequency acoustic waves to be reflected back to the probe. In autoimmune thyroid diseases (AITDs), however, both lymphocytic infiltration and disruption of normal tissue architecture cause a reduction in thyroid echogenicity (1,4,6,10,11). Thyroid hypoechogenicity is currently viewed as an early sign of thyroid autoimmunity, which may be present even when the thyroid disorder is not suspected from a clinical point of view (4,6,7,12,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interface between thyroid cells and the colloid exhibits an elevated acoustic impedance, causing high-frequency acoustic waves to be reflected back to the probe. In autoimmune thyroid diseases (AITDs), however, both lymphocytic infiltration and disruption of normal tissue architecture cause a reduction in thyroid echogenicity (1,4,6,10,11). Thyroid hypoechogenicity is currently viewed as an early sign of thyroid autoimmunity, which may be present even when the thyroid disorder is not suspected from a clinical point of view (4,6,7,12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Rapid improvements in US equipment and the use of standardized computerized algorithms have permitted an objective and quantitative measurement of tissue echogenicity in thyroid diseases (11)(12)(13), as well as in other pathological conditions (14,15). Using a subjective measure of thyroid echogenicity, previous studies demonstrated that in patients with thyroid autoimmune diseases, the presence of circulating thyroid antibodies (Abs) as well as the development of hypothyroidism was closely correlated with the degree of thyroid hypoechogenicity (1,5,11,12,16).…”
Section: Introductionmentioning
confidence: 99%
“…The change in echogenicity has also been demonstrated in subclinical (mild) hypothyroidism (1)(2)(3). Since subclinical thyroid dysfunction has a tendency to develop into overt thyroid dysfunction (4), the finding of decreased echogenicity or irregularity in echo pattern at thyroid US in these patients with the elevation of thyroid-stimulating hormone (TSH) could perhaps be seen as an early sign of thyroid failure.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, their presence is related to subclinical hypothyroidism and levels of thyroid autoantibodies (64,65), and ultrasonography has been used for the follow-up of patients (66). Thyroid ultrasonography is usually heterogeneous because of fibrosis and hypoechogenic areas, it is not necessary for diagnosis but it is recommended to confirm the presence of a thyroid nodule, solitary or multiple nodule can be detected both hypothyroid or euthyroid patients.…”
Section: Imagingmentioning
confidence: 99%